Utilization of Acacia Leaf Litter (Acacia Mangium) as an Eco-Friendly Composite Material - Rahmi Putri Wirman; Aldri Frinaldi; Dasman Lanin; Vandri Ahmad Isnaini (Science and Environmental Journal for Postgraduate, 2022)
This study discusses the parameters of Acacia leaf litter fibers in environmentally friendly composite mixtures. This parameter is used as a reference for whether Acacia leaf litter fibers have the potential to be additives to composites. The composite sample used in this study was concrete. Acacia tree leaves are leaves that have strong fibers and high resistance. Acacia trees are trees that grow rapidly and can multiply rapidly throughout the annual season in the tropics. Acacia leaf litter fibers are used as additives to produce strong and environmentally friendly composites. Testing Acacia leaf litter fiber parameters in the form of particle distribution in samples and fiber tensile tests using a Universal Testing Machine (UTM). ImageJ software carried out an analysis of the distribution of concrete constituent particles. From the analysis results, the average distribution of fine aggregate particles was 0,20 mm², coarse aggregates were 92.69 mm², and Acacia leaf fibers were 0.162 mm² for powder particles and 0.174 mm for thread-shaped particles (fiber diameter). The study results show that Acacia leaf fiber has a tensile test with a value of 6.38 kg/cm², which has good elasticity and durability so that it can be used as a composite mixture material.